The Missing Link: Integrating Interventional Pain Management in the Era of Multimodal Oncology - Alberto Corriero; Mariateresa Giglio; Rossana Soloperto; Angela Preziosa; Cristina Stefanelli; Mariapaola Castaldo; Federica Gloria; Antonella Paladini; Vittorio A. Guardamagna; Filomena Puntillo (Pain and Therapy)
Abstract Cancer-related pain (CrP) is one of the most frequent and debilitating issues that affect the quality of life of patients with cancer. Systemic analgesics, particularly opioids, have been the cornerstone of pain management. However, the following shortcomings of the mentioned therapies, such as side effects, tolerance, and inadequate relief in refractory cases, make implementing a more complete, multimodal treatment plan necessary. Interventional pain management (IPM) uses specific invasive procedures, with different degree of invasiveness, such as nerve blocks, neurolysis, neuromodulation, and intrathecal drug delivery systems to provide effective pain relief with reduced adverse effects compared with opioids. These approaches are frequently underutilized due to delayed referrals, insufficient awareness, and logistic inefficiencies, which delay access to pain management centers specializing in care for patients in pain. Recent technological advancements offer the potential to overcome these barriers, including artificial intelligence-driven decision support systems and automated referral pathways, enabling early intervention and individualized pain treatment plans. The future of CrP management should shift from the current reactive model to a proactive approach, enabling the earlier incorporation of interventional techniques into treatment plans. The integration of interdisciplinary collaboration and technological innovations will enhance cancer pain management and progress from current outdated approaches to provide more effective and timely pain relief for patients with chronic refractory cancer pain.